2018
DOI: 10.1016/j.contraception.2017.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Older teen attitudes toward birth control access in pharmacies: a qualitative study

Abstract: Several states recently passed legislation enabling pharmacists to prescribe contraception and other states are considering similar legislation. Older teens are interested in this additional method of contraceptive access and understanding their perspectives can help guide implementation by states and in individual pharmacies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 20 publications
(23 reference statements)
2
30
0
Order By: Relevance
“…A small 2018 survey of 18-and 19-year-old participants found that many supported increased access to contraception through the pharmacy. 9 Participants identified privacy, cost, and confidentiality as important features of pharmacist-provided contraceptive services.…”
mentioning
confidence: 99%
“…A small 2018 survey of 18-and 19-year-old participants found that many supported increased access to contraception through the pharmacy. 9 Participants identified privacy, cost, and confidentiality as important features of pharmacist-provided contraceptive services.…”
mentioning
confidence: 99%
“…Ultimately, six articles reporting data from four studies met the inclusion criteria and were included in the effectiveness review 9–14. An additional 24 articles from 23 studies were included in the values and preferences review 13 15–37…”
Section: Resultsmentioning
confidence: 99%
“…We identified 24 articles from 23 studies that met the inclusion criteria for the values and preferences review. Of these, 13 articles focused on the perspectives of female OC users, potential users, or women in general,13 15 16 18 19 21–24 29–31 37 9 focused on the perspectives of healthcare providers (particularly physicians) and pharmacists17 25 26 28 32–36 3839 and 1 focused on the general public;27 one article included both women and healthcare providers 20. Almost all studies were conducted in the USA, except for one each in Canada,32 France17 and Ireland15; one publication from the Border Contraceptive Access Study included in the values and preferences review included women residing in El Paso, Texas, who accessed OCs in both the USA and Mexico 13.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At a clinical and policy level, it is essential to ensure that women have access to affordable or no-cost contraception at any age. Over-the-counter contraception or ensuring parent consent is not required for any family planning service including abortion, and more targeted education in schools, can help address this at the policy level [21][22][23]. Mothers and fathers are often the gate-keepers to this information and access, but, as noted by many participants, can often put up barriers themselves.…”
Section: Discussionmentioning
confidence: 99%